Preparation method of tantalum bar
By using technical means of gradient pressure and gradient temperature during the preparation of tantalum strips, the problem of insufficient density and flatness of tantalum strips is solved, and its performance is significantly improved, making it more suitable for use in the semiconductor IC industry.
Patent Information
- Application Number
- CN202411401747.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively improve the density and flatness of tantalum strips, which affects its application in the semiconductor IC industry.
The cold isostatic pressure and the gradient temperature program are used to improve the density consistency and flatness of the edges and cores of the tantalum strips, respectively.
Through the combination of gradient pressure and gradient temperature, the density and flatness of the tantalum strips are significantly improved, making them more suitable for the preparation of IC tantalum targets.
Smart Images

Figure CN119457040A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of metal processing technology, and in particular to a method for preparing a tantalum bar. Background Art
[0002] In the chip manufacturing process, the raw material for the sputtering coating of the core process is high-purity metal targets. In the 65nm, 45nm and the most advanced 7nm line width processes, copper (Cu) interconnection technology gradually replaces aluminum (Al) interconnection technology. Tantalum (Ta) targets are used for sputtering to form a diffusion barrier layer for copper interconnection, which can prevent copper atoms from diffusing into the silicon (Si) matrix and causing a decrease in current density and performance of components. They are widely used in chemical, microelectronics, electrical and other industrial fields. Tantalum targets have gradually become one of the key raw materials in the semiconductor industry.
[0003] As the semiconductor IC (integrated circuit) industry develops and Moore's Law continues, the process is becoming more and more advanced, the metal line width requirements are becoming finer and finer, and the purity of raw materials is required to be higher. Therefore, there are strict requirements for the raw materials of IC tantalum targets. At present, IC tantalum targets are mainly prepared by vacuum electron beam melting of high-purity tantalum bars (i.e. tantalum rods). The density and flatness of the tantalum bars have a great impact on the performance of IC tantalum targets. Therefore, it is urgent to develop a technology to improve the density and flatness of the tantalum bars. Summary of the invention
[0004] Based on the defects of the prior art, the purpose of this application is to provide a method for preparing tantalum bars to improve the density and flatness of the tantalum bars.
[0005] To achieve the above object, the present application provides a method for preparing a tantalum bar, comprising the following steps:
[0006] Providing tantalum powder, loading the tantalum powder into a mold, vibrating, sealing, cold isostatic pressing, demolding, and vacuum sintering to obtain a tantalum bar;
[0007] Wherein, the cold isostatic pressing adopts a gradient pressure program, and the vacuum sintering adopts a gradient temperature program.
[0008] The inventor found in the research process that cold isostatic pressing with a gradient pressure program can help improve the consistency of shrinkage between the edge and the core of the powder, making the density of the edge and the core of the tantalum bar closer, thereby improving the flatness of the tantalum bar; vacuum sintering with a gradient temperature program can reduce the difference in density between the core and the edge of the tantalum bar and improve its flatness. By combining cold isostatic pressing with a gradient pressure degree and vacuum sintering with a gradient temperature program, the resulting tantalum bar has a higher density and better flatness.
[0009] Preferably, the pressure program of the cold isostatic pressing is as follows:
[0010] 5-10min from 0-0.11MPa to the first pressure, maintain pressure for 5-10min;
[0011] 10-20 minutes to increase from the first pressure to the second pressure, and maintain the pressure for 10-20 minutes;
[0012] 20-30 minutes to increase from the second pressure to the third pressure, and maintain the pressure for 20-30 minutes;
[0013] Wherein, the first pressure is 30-80 MPa, the second pressure is 100-180 MPa, and the third pressure is 200-300 MPa.
[0014] The cold isostatic pressing is performed by adopting the above-mentioned specific gradient pressure increasing method, so that the flatness of the obtained tantalum bar is higher.
[0015] Preferably, the temperature program of the vacuum sintering is as follows:
[0016] 1-5h from room temperature to the first temperature, keep warm for 1-5h;
[0017] 2-6h from the first temperature to the second temperature, and keep warm for 2-6h;
[0018] 3-10h from the second temperature to the third temperature, and keep warm for 3-10h;
[0019] Wherein, the first temperature is 800-1000°C, the second temperature is 1200-1500°C, and the third temperature is 1700-2300°C.
[0020] By adopting the above-mentioned specific gradient temperature rise program for sintering, the obtained tantalum bar has better sintering shrinkage and densification state and better flatness.
[0021] Herein, "room temperature" refers to 0°C-30°C, such as 0°C, 5°C, 10°C, 15°C, 20°C, 25°C, 30°C or an interval formed by any two of the above values.
[0022] Preferably, the tantalum powder has a Fisher particle size of 2-15 μm, a porosity of 50%-75%, and an apparent density of 2-6 g / cm 3 .
[0023] During the research process, the inventors found that the Fisher grain size, porosity and apparent density of tantalum powder will affect its slip and deformation shrinkage in subsequent processes, and thus affect the density and flatness of the obtained tantalum bars. By controlling the Fisher grain size, porosity and apparent density of tantalum powder within the above-mentioned suitable range, it is beneficial to obtain tantalum bars with high density and good flatness, and reduce the defects of tantalum bars.
[0024] The Fisher particle size of the tantalum powder can be selected as 2μm, 4μm, 6μm, 8μm, 10μm, 12μm, 14μm, 15μm or an interval formed by any two of the above values. The Fisher particle size of the tantalum powder can be measured by using a Fisher particle size detector using a steady-flow air permeation method.
[0025] The porosity of the tantalum powder can be selected to be 50%, 52%, 55%, 57%, 60%, 60%, 65%, 67%, 70%, 72%, 75% or an interval formed by any two of the above values. The porosity of the tantalum powder can be measured by using a Fisher particle size detector using a steady-flow air permeation method.
[0026] The bulk density of the tantalum powder can be selected to be 2g / cm 3 , 2.5g / cm 3 , 3g / cm 3 、3.5g / cm 3 , 4g / cm 3 , 4.5g / cm 3 , 5g / cm 3 , 5.5g / cm 3 , 6g / cm 3 Or the interval formed by any two of the above values. The bulk density of the tantalum powder can be measured by a powder bulk density tester.
[0027] Preferably, the purity of the tantalum powder is 99.95wt.% to 100wt.%. Using the tantalum powder of the above purity as the raw material can make the purity of the obtained tantalum bar be above 99.95wt.%.
[0028] In some embodiments, the method for preparing tantalum powder comprises the following steps:
[0029] (1) Potassium fluorotantalate and diluent sodium chloride are charged into a reaction kettle at a mass ratio of (1-10):1, and after evacuation, argon gas is introduced to a positive pressure (0.1-0.17 MPa), and the reaction kettle is placed in a reduction furnace;
[0030] (2) Raise the temperature to 400-700°C, keep the temperature and start the stirring equipment, inject sodium, the mass of sodium injection is 5%-30% of the mass of potassium fluorotantalate, the injection speed is 1-5 kg / min, keep the temperature for 1-3 hours and cool naturally;
[0031] (3) coarsely crushing the reduced product by a jaw crusher;
[0032] (4) first wash with water to remove the residual sodium and unreduced potassium fluorotantalate, the byproducts of the reaction NaF and KF, and the diluent that does not participate in the reaction, and then use the HNO3+HF pickling system for pickling treatment to reduce the metal impurities (Fe, Ni, Cr, etc.) and non-metallic impurities in the tantalum powder;
[0033] (5) vacuum drying, sieving the powder with a 40-125 mesh sieve to obtain the reduced original powder;
[0034] (6) Vacuum heat treatment: vacuum degree 2×10 -3 Pa~8×10 -3 Pa, temperature 1000~1400℃, holding time 1~4h.
[0035] Preferably, the vacuum degree of the vacuum sintering is ≤5×10 -2 More preferably, the vacuum degree of the vacuum sintering is 3×10 -2 Pa-1×10 -2 Pa.
[0036] Preferably, the density of the tantalum bar is ≥95% and the flatness is ≤10 mm.
[0037] Preferably, the density of the tantalum bar is 95%-99% and the flatness is 3-7 mm.
[0038] The density of the tantalum bar can be measured according to the water displacement method; the flatness can be measured by using a knife edge ruler or a marble platform.
[0039] Preferably, the cross section of the tantalum bar is square or rectangular. Here, "cross section of the tantalum bar" refers to a plane figure obtained by cutting along a direction perpendicular to the long axis of the tantalum bar. The cross section of the tantalum bar is square or rectangular, which facilitates better stacking and bundling of the tantalum bar or electrode welding during electron beam melting.
[0040] Preferably, the mold comprises a hard outer shell and a soft inner shell disposed in the hard outer shell;
[0041] The hard outer cover and the soft inner cover each include a body and an opening portion provided at one end of the body;
[0042] The body of the hard outer jacket is provided with a plurality of through holes arranged at intervals;
[0043] The opening of the soft inner sleeve is sealed by a sealing member.
[0044] Preferably, the opening of the soft inner sleeve is cylindrical and sealed with a cylindrical seal, and the cylindrical seal is also locked by a locking member. Strengthening the fixation with the locking member can make the mold sealing effect better, prevent oil leakage, increase the product qualification rate, and reduce production costs.
[0045] Preferably, the cross-section of the body of the soft inner sleeve and the hard outer sleeve is square or rectangular.
[0046] Preferably, the material of the soft inner sleeve is at least one of polyurethane, nitrile rubber and latex, and the material of the hard outer sleeve is steel.
[0047] Preferably, the opening of the hard outer shell is provided with a transverse extension portion, and the transverse extension portion is provided with a lifting ring, so as to facilitate lifting, improve work efficiency, and reduce safety risks during personnel handling.
[0048] Compared with the prior art, the beneficial effect of the present application is that the pressure program of cold isostatic pressing and the temperature program of vacuum sintering are both gradients, so as to reduce the density difference between the core and edge parts of the tantalum bar, improve its flatness and density, and make it suitable for preparing IC tantalum targets. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 Schematic diagram of the mold structure used for cold isostatic pressing in each embodiment;
[0050] Figure 2 Flowchart of the tantalum bar preparation process of each embodiment. DETAILED DESCRIPTION
[0051] In order to better illustrate the purpose, technical scheme and advantages of the present application, the present application will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present application in detail, rather than to limit the present application. All other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. The experimental reagents and instruments involved in the implementation of the present application are all commonly used ordinary reagents and instruments unless otherwise specified.
[0052] The schematic diagram of the mold structure used for cold isostatic pressing in the following embodiments is as follows Figure 1 Said, it comprises a hard outer shell and a soft inner shell placed in the hard outer shell;
[0053] The hard outer cover and the soft inner cover both include a body and an opening portion provided at one end of the body;
[0054] The material of the hard outer jacket is steel, the main body is provided with a plurality of through holes arranged at intervals, the opening is provided with a transverse extension part, and the transverse extension part is provided with a lifting ring;
[0055] The material of the soft inner sleeve is nitrile rubber, the opening is cylindrical, and is sealed with a cylindrical rubber plug, which is locked by a throat clamp;
[0056] The cross sections of the hard outer shell and the soft inner shell body are both square.
[0057] Example 1
[0058] This embodiment provides a method for preparing a tantalum bar, comprising the following steps:
[0059] ① Provide tantalum powder with a purity of 99.7wt.%, a Fisher particle size of 8μm, a porosity of 60%, and a bulk density of 4g / cm 3 ;
[0060] ②Put the above tantalum powder into the soft inner sleeve and vibrate it, seal it with a square rubber plug first, then seal the opening with a cylindrical rubber plug, and then lock the cylindrical rubber plug with a throat clamp, then wrap it with 8 layers of wrapping film, place the soft inner sleeve in the hard outer sleeve for cold isostatic pressing, and then demold to obtain the tantalum green body. Inspection shows that the mold is well sealed and there is no oil in the tantalum green body. The pressure procedure for cold isostatic pressing is as follows:
[0061] The pressure was raised from 0MPa to 50MPa at a constant speed over 7 minutes, and the pressure was maintained for 7 minutes.
[0062] Increase the pressure from 50MPa to 150MPa at a constant speed over 15 minutes, and maintain the pressure for 15 minutes.
[0063] Increase the pressure from 150MPa to 250MPa at a constant speed over 25 minutes, and maintain the pressure for 25 minutes.
[0064] ③ The tantalum green body is vacuum sintered, and the vacuum degree during the vacuum sintering process is 4×10 -2 Pa, the temperature program is as follows:
[0065] The temperature was raised from 25°C to 900°C at a constant speed over 3 hours, and kept at this temperature for 3 hours;
[0066] The temperature was raised from 900°C to 1300°C at a constant speed over 4 hours, and kept at this temperature for 4 hours;
[0067] 6h uniformly increase the temperature from 1300℃ to 2000℃, keep warm for 7h;
[0068] After sintering, tantalum bars are obtained.
[0069] The method for preparing the tantalum powder used in this embodiment comprises the following steps:
[0070] (1) Potassium fluorotantalate and diluent sodium chloride are placed in a reaction kettle at a mass ratio of 5:1, argon is introduced into the reaction kettle to a positive pressure (0.15 MPa) after evacuation, and the reaction kettle is placed in a reduction furnace;
[0071] (2) Raise the temperature to 500°C, keep the temperature and start the stirring equipment, inject sodium, the mass of sodium injection is 15% of the mass of potassium fluorotantalate, the injection rate is 2 kg / min, keep the temperature for 1 hour and cool naturally;
[0072] (3) coarsely crushing the reduced product by a jaw crusher;
[0073] (4) first wash with water to remove the residual sodium and unreduced potassium fluorotantalate, the byproducts of the reaction NaF and KF, and the diluent that does not participate in the reaction, and then use the HNO3+HF pickling system for pickling treatment to reduce the metal impurities (Fe, Ni, Cr, etc.) and non-metallic impurities in the tantalum powder;
[0074] (5) vacuum drying, sieving the powder with an 80-mesh sieve to obtain the reduced original powder;
[0075] (6) Vacuum heat treatment: vacuum degree 2×10 -3 Pa, temperature 1300℃, holding time 3h.
[0076] Example 2
[0077] This embodiment provides a method for preparing a tantalum bar. The method for preparing a tantalum bar in this embodiment is different from that in embodiment 1 in that the pressure procedure of the cold isostatic pressing in step ② is as follows:
[0078] The pressure was raised from 0MPa to 30MPa at a constant speed over 5 minutes, and the pressure was maintained for 5 minutes.
[0079] Increase the pressure from 30MPa to 100MPa at a constant speed over 10 minutes, and maintain the pressure for 10 minutes.
[0080] Increase the pressure uniformly from 100MPa to 200MPa in 20min and maintain the pressure for 20min.
[0081] Example 3
[0082] This embodiment provides a method for preparing a tantalum bar. The method for preparing a tantalum bar in this embodiment is different from that in embodiment 1 in that the pressure procedure of the cold isostatic pressing in step ② is as follows:
[0083] The pressure was raised from 0MPa to 80MPa at a constant speed over 10 minutes, and the pressure was maintained for 10 minutes.
[0084] The pressure was raised from 80MPa to 180MPa at a constant speed over 10 minutes, and maintained for 20 minutes.
[0085] Increase the pressure uniformly from 180MPa to 300MPa in 30 minutes and maintain the pressure for 30 minutes.
[0086] Example 4
[0087] This embodiment provides a method for preparing a tantalum bar. The method for preparing a tantalum bar in this embodiment is different from that in embodiment 1 in that the pressure procedure of the cold isostatic pressing in step ② is as follows:
[0088] The pressure was increased from 0 MPa to 150 MPa at a constant speed over 22 minutes, and maintained for 22 minutes;
[0089] Increase the pressure from 150MPa to 250MPa at a constant speed over 25 minutes and maintain the pressure for 25 minutes.
[0090] Example 5
[0091] This embodiment provides a method for preparing a tantalum bar. The method for preparing a tantalum bar in this embodiment is different from that in embodiment 1 in that the pressure procedure of the cold isostatic pressing in step ② is as follows:
[0092] Increase the pressure from 0MPa to 50MPa at a constant speed over 7 minutes, and maintain the pressure for 7 minutes;
[0093] Increase the pressure from 150MPa to 250MPa at a constant speed over 40min and maintain the pressure for 40min.
[0094] Example 6
[0095] This embodiment provides a method for preparing a tantalum bar. The difference between the method for preparing a tantalum bar in this embodiment and that in embodiment 1 is that the temperature program of the vacuum sintering process in step ③ is as follows:
[0096] Increase the temperature uniformly from 0℃ to 800℃ in 1h, and keep it warm for 5h;
[0097] 2h uniformly increase the temperature from 800℃ to 1200℃, keep the temperature for 6h;
[0098] Increase the temperature uniformly from 1200℃ to 1700℃ in 3h and keep it at this temperature for 10h.
[0099] Example 7
[0100] This embodiment provides a method for preparing a tantalum bar. The difference between the method for preparing a tantalum bar in this embodiment and that in embodiment 1 is that the temperature program of the vacuum sintering process in step ③ is as follows:
[0101] Increase the temperature from 30°C to 1000°C at a constant speed over 5 hours, and keep it warm for 1 hour;
[0102] 6h uniformly increase the temperature from 1000℃ to 1500℃, keep warm for 2h;
[0103] Increase the temperature uniformly from 1500℃ to 2300℃ for 10h and keep warm for 3h.
[0104] Example 8
[0105] This embodiment provides a method for preparing a tantalum bar. The difference between the method for preparing a tantalum bar in this embodiment and that in embodiment 1 is that the temperature program of the vacuum sintering process in step ③ is as follows:
[0106] The temperature was raised from room temperature to 900°C at a constant speed over 3 hours, and kept at this temperature for 3 hours;
[0107] The temperature was raised uniformly from 900°C to 2000°C in 10 hours and kept at this temperature for 11 hours.
[0108] Example 9
[0109] This embodiment provides a method for preparing a tantalum bar. The difference between the method for preparing a tantalum bar in this embodiment and that in embodiment 1 is that the temperature program of the vacuum sintering process in step ③ is as follows:
[0110] 7h uniformly raise the temperature from room temperature to 1300℃, keep warm for 7h;
[0111] The temperature was raised from 1300°C to 2000°C at a constant speed for 6 hours and kept at this temperature for 7 hours.
[0112] Example 10
[0113] This embodiment provides a method for preparing a tantalum bar. The method for preparing a tantalum bar in this embodiment is different from that in embodiment 1 in that the tantalum powder provided in step ① has a Fisher particle size of 2 μm, a porosity of 50%, and an apparent density of 6 g / cm 3 .
[0114] The method for preparing tantalum powder used in this embodiment is different from the method for preparing tantalum powder used in Example 1 in that the mesh size of the sieve used in step (5) is 125 meshes.
[0115] Embodiment 11
[0116] This embodiment provides a method for preparing a tantalum bar. The method for preparing a tantalum bar in this embodiment is different from that in embodiment 1 in that the tantalum powder provided in step ① has a Fisher particle size of 15 μm, a porosity of 75%, and an apparent density of 2 g / cm 3 .
[0117] The method for preparing tantalum powder used in this embodiment is different from the method for preparing tantalum powder used in Example 1 in that the mesh size of the sieve used in step (5) is 40 mesh; and the vacuum heat treatment temperature in step (6) is 1000°C.
[0118] Example 12
[0119] This embodiment provides a method for preparing a tantalum bar. The method for preparing a tantalum bar in this embodiment is different from that in embodiment 1 in that the tantalum powder provided in step ① has a Fisher particle size of 20 μm, a porosity of 65%, and an apparent density of 5.5 g / cm 3 .
[0120] The method for preparing tantalum powder used in this embodiment is different from the method for preparing tantalum powder used in Example 1 in that the mesh size of the sieve used in step (5) is 60 mesh; the vacuum heat treatment temperature in step (6) is 1300°C, and the insulation time is 2h.
[0121] Embodiment 13
[0122] This embodiment provides a method for preparing a tantalum bar. The method for preparing a tantalum bar in this embodiment is different from that in embodiment 1 in that the tantalum powder provided in step ① has a Fisher particle size of 10 μm, a porosity of 35%, and an apparent density of 5.5 g / cm 3 .
[0123] The difference between the preparation method of tantalum powder used in this embodiment and the preparation method of tantalum powder used in Example 1 is that the mesh size of the sieve used in step (5) is 60 mesh; and the vacuum heat treatment temperature in step (6) is 1450°C.
[0124] Embodiment 14
[0125] This embodiment provides a method for preparing a tantalum bar. The method for preparing a tantalum bar in this embodiment is different from that in embodiment 1 in that the tantalum powder provided in step ① has a Fisher particle size of 6 μm, a porosity of 65%, and an apparent density of 10 g / cm 3 .
[0126] The difference between the preparation method of tantalum powder used in this embodiment and the preparation method of tantalum powder used in Example 1 is that the mesh size of the sieve used in step (5) is 100 mesh; and the vacuum heat treatment temperature in step (6) is 1400°C.
[0127] Embodiment 15
[0128] This embodiment provides a method for preparing a tantalum bar. The method for preparing a tantalum bar in this embodiment is different from that in embodiment 1 in that the tantalum powder provided in step ① has a Fisher particle size of 1 μm, a porosity of 65%, and an apparent density of 5.5 g / cm 3 .
[0129] The method for preparing tantalum powder used in this embodiment is different from the method for preparing tantalum powder used in Example 1 in that the mesh size of the sieve used in step (5) is 125 meshes.
[0130] Comparative Example 1
[0131] This comparative example provides a method for preparing a tantalum bar. The difference between the method for preparing a tantalum bar in this comparative example and that in Example 1 is that the pressure procedure of the cold isostatic pressing in step ② is as follows:
[0132] The pressure increased from 0MPa to 250MPa at a constant speed over 47 minutes and the pressure was maintained for 47 minutes.
[0133] Comparative Example 2
[0134] This comparative example provides a method for preparing a tantalum bar. The difference between the method for preparing a tantalum bar in this comparative example and that in Example 1 is that the temperature program of the vacuum sintering process in step ③ is as follows:
[0135] The temperature was raised from room temperature to 2000℃ at a constant rate of 13h and kept at this temperature for 14h.
[0136] The tantalum bars obtained in the above examples and comparative examples were subjected to the following performance tests:
[0137] Density: measured by displacement method;
[0138] Flatness: Use a knife-edge ruler to measure flatness.
[0139] The test results are shown in Table 1.
[0140] Table 1
[0141] Density / % Flatness / mm Example 1 98.86% 3 Example 2 98.25% 3.5 Example 3 97.93% 4.1 Example 4 97.65% 4.4 Example 5 96.43% 5.3 Example 6 97.2% 3.9 Example 7 97.1% 4.2 Example 8 96.6% 4.5 Example 9 96.1% 5.8 Example 10 97.3% 3.3 Embodiment 11 97.1% 4.5 Example 12 96.2% 4.9 Embodiment 13 95.6% 5.1 Embodiment 14 95.6% 4.3 Embodiment 15 95.8% 5.0 Comparative Example 1 83.34% 11 Comparative Example 2 85.65% 14
[0142] From the above data, it can be seen that the density of the tantalum bars obtained in each embodiment of the present application is ≥95%, and the flatness is ≤10mm. Among them, when the Fisher particle size of the raw material tantalum powder used is 2-15μm, the porosity is 50%-75%, and the apparent density is 2-6g / cm 3 The density and flatness of the obtained tantalum bar are better. The pressure program of cold isostatic pressing used in Comparative Example 1 is not a gradient, which leads to a large difference in shrinkage between the powder at the edge and the powder at the core of the blank during cold isostatic pressing, a large difference in density, a deviation in flatness of the tantalum bar, and a deviation in density. The temperature program of vacuum sintering used in Comparative Example 2 is not a gradient, which leads to a large difference in density between the edge and the core of the blank during vacuum sintering, a deviation in flatness of the tantalum bar, and a deviation in density.
[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A method for preparing a tantalum bar, characterized in that: The following steps are involved: Providing tantalum powder, loading the tantalum powder into a mold, vibrating, sealing, cold isostatic pressing, demolding, and vacuum sintering to obtain a tantalum bar; Wherein, the cold isostatic pressing adopts a gradient pressure program, and the vacuum sintering adopts a gradient temperature program.
2. The method for preparing a tantalum bar according to claim 1, characterized in that: The pressure procedure of the cold isostatic pressing is as follows: 5-10min from 0-0.11MPa to the first pressure, maintain pressure for 5-10min; 10-20 minutes to increase from the first pressure to the second pressure, and maintain the pressure for 10-20 minutes; 20-30 minutes to increase from the second pressure to the third pressure, and maintain the pressure for 20-30 minutes; Wherein, the first pressure is 30-80 MPa, the second pressure is 100-180 MPa, and the third pressure is 200-300 MPa.
3. The method for preparing a tantalum bar according to claim 1, characterized in that: The temperature program of the vacuum sintering is as follows: 1-5h from room temperature to the first temperature, keep warm for 1-5h; 2-6h from the first temperature to the second temperature, and keep warm for 2-6h; 3-10h from the second temperature to the third temperature, and keep warm for 3-10h; Wherein, the first temperature is 800-1000°C, the second temperature is 1200-1500°C, and the third temperature is 1700-2300°C.
4. The method for preparing a tantalum bar according to claim 1, characterized in that: The tantalum powder has a Fisher particle size of 2-15 μm, a porosity of 50%-75%, and a bulk density of 2-6 g / cm 3 .
5. The method for preparing a tantalum bar according to claim 1, characterized in that: The purity of the tantalum powder is 99.95wt.% to 100wt.%.
6. The method for preparing a tantalum bar according to claim 1, characterized in that: The vacuum degree of the vacuum sintering is ≤5×10 - 2 Pa, preferably 3×10 -2 Pa-1×10 -2 Pa.
7. The method for preparing a tantalum bar according to claim 1, characterized in that: The density of the tantalum bar is ≥95%, and the flatness is ≤10mm; preferably, the density of the tantalum bar is 95%-99%, and the flatness is 3-7mm.
8. The method for preparing a tantalum bar according to claim 1, characterized in that: The cross section of the tantalum bar is square or rectangular.
9. The method for preparing a tantalum bar according to claim 1, characterized in that: The mold comprises a hard outer shell and a soft inner shell placed in the hard outer shell; The hard outer cover and the soft inner cover each include a body and an opening portion provided at one end of the body; The body of the hard outer jacket is provided with a plurality of through holes arranged at intervals; The opening of the soft inner sleeve is sealed by a sealing member.
10. The method for preparing a tantalum bar according to claim 9, characterized in that: At least one of the following conditions is met: (1) The opening of the soft inner sleeve is cylindrical and sealed by a cylindrical seal, and the cylindrical seal is also locked by a locking member; (2) The cross-section of the soft inner sleeve and the hard outer sleeve is square or rectangular; (3) The material of the soft inner sleeve is at least one of polyurethane, nitrile rubber, and latex, and the material of the hard outer sleeve is steel; (4) The opening of the hard outer shell is provided with a lateral extension portion, and the lateral extension portion is provided with a hanging ring.